Pirolisis Reject Pulp Menjadi Bio-Oil Dengan menggunakan Katalis NI/NZA (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The using and utilization ofÂ bio-oil became the main alternative to overcome the problem of dependence on fuel. Bio-oil can be produced from the pyrolysis of reject pulp. Reject pulp can be converted into bio-oil through a pyrolysis process using a Ni/NZA catalyst. The variation of the reaction temperature 290oC, 300oC, 310oC and 320oC. The weight ratio of catalyst with biomass was varied at 0%; 1%; 2%; dan 3%. The pyrolysis processing used nitrogen gas with a flow rate of 80 ml/min. The yield of maximum product was gotten such 88.2%. The bio-oil composition dominance obtained 24,65% Hydroxyl acetone, 22,35% Acetone alcohol, 19,1% Acetic acid, 5,5% 2,3-Dimethyl-2-cyclopenten-1-one and 3,09% 1-Hydroxy-2- butanone. Â Key Words: Bio-oil, Reject pulp, Ni/NZA, Pyrolysis